Broadband 1H homodecoupled NMR experiments: recent developments, methods and applications. (21st April 2015) - Castañar, Laura; Parella, Teodor
<x xml:space="preserve">Abstract</x> In recent years, a great interest in the development of new broadband 1H homonuclear decoupled techniques providing simplified JHH multiplet patterns has emerged again in the field of small molecule NMR. The resulting highly resolved 1H NMR spectra display resonances as collapsed singlets, therefore minimizing signal overlap and expediting spectral analysis. This review aims at presenting the most recent advances in pure shift NMR spectroscopy, with a particular emphasis to the Zangger–Sterk experiment. A detailed discussion about the most relevant practical aspects in terms of pulse sequence design, selectivity, sensitivity, spectral resolution and performance is provided. Finally, the implementation of the different reported strategies into traditional 1D and 2D NMR experiments is described while several practical applications are also reviewed. Copyright © 2015 John Wiley & Sons, Ltd.